Anionic Chains of Parent Pnictogenylboranes. Issue 47 (25th October 2016) - Marquardt, Christian; Kahoun, Tobias; Stauber, Andreas; Balázs, Gábor; Bodensteiner, Michael; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: We report on the synthesis and structural characterization of unprecedented anionic parent compounds of mixed Group 13/15 elements. The reactions of the pnictogenylboranes H2 E‐BH2 ⋅NMe3 (1 a =P, 1 b =As) with phosphorus and arsenic centered nucleophiles of the type [EH2 ] − (E=P, As) lead to the formation of compounds of the type [H2 E‐BH2 ‐E′H2 ] − (2 : E=E′=P; 3 : E=E′=As; 4 : E=P, E′=As) containing anionic pnictogen–boron chain‐like units. Furthermore, a longer 5‐membered chain species [H2 As‐BH2 ‐PH2 ‐BH2 ‐AsH2 ] − (5 ) and a cyclic compound [NHC dipp ‐H2 B‐PH2 ‐BH2 ‐NHC dipp ] + [P5 B5 H19 ] − (6 ) containing a n ‐butylcyclohexane‐like anion were obtained. All the compounds have been characterized by X‐ray structure analysis, multinuclear NMR spectroscopy, IR spectroscopy, and mass spectrometry. DFT calculations elucidate their high thermodynamic stability, the charge distribution, and give insight into the reaction pathway. Abstract : Finally, thoroughly negative ! Using alkali‐metal salts of phosphanide and arsenide, the parent compounds of the phosphanyl‐ and arsanylboranes can be easily converted into linear anionic chain molecules. They are unique representatives of the anionic class of pnictogenylboranes and could be structurally characterized.